Reconstruction of Abandoned Apartment on Ahmad Yani Street, Cirebon City - Dika Hidayatullah; Firman Audyraja Permana; Riyan Setiawan Mandala Putra; Tira Roesdiana (CV. Syntax Corporation Indonesia, 2026)
Apartments can be used as an efficient vertical housing solution in the midst of limited land in urban areas. However, not all apartment projects were successfully completed as planned, such as a 12-storey apartment building on Ahmad Yani street, Cirebon City, which was abandoned and needed structural redesign so that it could be re-functional. This research aims to redesign the structure of apartment buildings using the latest planning standards, namely SNI 2847-2019 (Structural Concrete Requirements), SNI 1726-2019 (Earthquake Resilience Planning), and SNI 1727-2020 (Minimum Building Load). The methods used include literature studies, primary and secondary data collection, structural modeling using software ETABS, as well as analysis and redesign of key elements such as plates, beams, and columns. The structural system applied is SRPMK (Sistem Rangka Pemikul Momen Khusus), Because the location of the building is included in the category of seismic design D. The calculation results show that the redesigned structural elements meet all technical criteria and structural safety requirements. The thickness of the plate is 200 mm meets the minimum limit based on the rigidity of the plate and beam. The dimensions of the beams and columns are determined to be able to withstand gravitational and lateral loads. Total load factored (DL + LL + earthquake) calculated and used as a basis in the planning of structural elements and foundations. With a design approach that complies with the latest regulations and technology, apartment buildings that were originally unused can now be revitalized into safe, decent housing, and support the development of the spatial layout of Cirebon city.